Biblioteca Astrid Cabral - Oliveira, Emanuelle Queiroz de (Brasil, 2022)
The reading habit in Brazil has been shown to be unstable as the number of readers decreases and more than half of the population claims to have never stepped into a library. In addition, data shows that many libraries in the country do not have the technological resources appropriate for current needs, and the absence of well-designed architectural spaces is also a determining factor for the lack of new visitors. To encourage the community to read and insert the library into the program of relevant activities in the city, a new approach is proposed for this project, with a more sensitive look at how the architecture of the built space can directly influence the behavior and well- being of its user, applying tactics to make the environment itself more interactive, playful and educational with the stimulus of the five senses.